2021
DOI: 10.1021/acsomega.0c04784
|View full text |Cite|
|
Sign up to set email alerts
|

Chemisorption and Physisorption of Water Vapors on the Surface of Lithium-Substituted Cobalt Ferrite Nanoparticles

Abstract: Ferrimagnetic materials have the assembly of n-type porous semiconductors that shows the evidence of several physical properties used in electronic devices and technology. If the water vapors are brought closer to the surface of n-type semiconductors, then the electrons near the surface of materials are transferred from the conduction band to the electron-accepting level of the water molecule that provides chemisorbed layer of OH– ions. The conduction of electrons takes place only when H3O+ releases one proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Another study also found that the size of the cobalt ferrite was tuned to the smallest particle diameter of 10 nm via changing the stoichiometry to acquire the optimal magnetic properties . In addition, previous studies also revealed that a particle diameter of ferrite (MFe 2 O 4 ) could be controlled by varying the surfactant ratio and doping ions, and a smaller particle size controls a variety of properties that are relevant to many potential applications. …”
Section: Resultsmentioning
confidence: 99%
“…Another study also found that the size of the cobalt ferrite was tuned to the smallest particle diameter of 10 nm via changing the stoichiometry to acquire the optimal magnetic properties . In addition, previous studies also revealed that a particle diameter of ferrite (MFe 2 O 4 ) could be controlled by varying the surfactant ratio and doping ions, and a smaller particle size controls a variety of properties that are relevant to many potential applications. …”
Section: Resultsmentioning
confidence: 99%
“…To calculate the actual density the radius, mass and thickness of the pellet were measured ( D a = (mass/volume). [ 24,25 ] The calculated dislocation density, the expected distance between magnetic ions ( L A and L B ), the X‐ray density D x , the actual density D a , and the porosity are shown in Table 2 . The dislocation density, L A and L B , varies with increasing concentration of magnesium as the lattice parameter.…”
Section: Resultsmentioning
confidence: 99%